Early analysis of surrogate endpoints for metastatic melanoma in immune checkpoint inhibitor trials. Issue 26 (June 2016) - Petrelli, Fausto; Coinu, Andrea; Cabiddu, Mary; Borgonovo, Karen; Ghilardi, Mara; Lonati, Veronica; Barni, Sandro
Abstract : Abstract: Recent major phase III trials led to the approval of immune checkpoint inhibitors (ipilimumab, pembrolizumab, and nivolumab) in metastatic malignant melanoma (MM). We aim to assess whether median progression-free survival, and 1 and 2-year overall survival (OS) rates are reliable surrogate endpoints for median OS through a meta-analysis of published trials involving immunotherapy. A systematic literature search in PubMed, EMBASE, Web of Science, and SCOPUS of published phase II to III trials with immunotherapy as the treatment for MM was conducted. Adjusted weighted linear regression was used to calculate Pearson correlations ( R ) between surrogates and median OS, and between treatment effects on surrogates and median OS. A total of 13 studies involving 3373 patients with MM were identified. The correlation of progression-free survival with OS was not significant ( R = 0.45, P = .11). Conversely, the correlation between 1-year OS and median OS was very strong ( R = 0.93, 95% confidence interval [CI] 0.84–0.96, P  < .00001), as was the correlation between 2-year OS and OS ( R = 0.79, 95% CI 0.51–0.91, P = .0001). The correlation between the treatment effects on 1-year OS and OS was also significant ( R = −0.86, 95% CI −0.3 to 0.97, P = .01). Similar results were obtained for 2-year OS. According to the available study data, 1-year OS rate could be regarded as a potential surrogate for median OS in novel immunotherapy trials of metastatic MM. Waiting for ongoing studies (e.g., pembrolizumab), we suggest that this intermediate endpoint could be considered as a potential primary endpoint in future clinical trials.